Evaluation of the Anti-Inflammatory Effect of Pioglitazone in Experimental Models of Inflammation in Rats - A. Sulaiman, Amaal; A. Hussain, Saad; M. Jum’ma, Kasim; H. Sigar, Assad (Iraqi Journal of Pharmaceutical Sciences, 2017)
The antidiabetic thiozolidinediones (TZDs) a class of peroxisome proliferators-activated receptor (PPAR) ligands has recently been the focus of much interest for their possible role in regulation of inflammatory response. The present study was designed to evaluate the anti-inflammatory activity of pioglitazone in experimental models of inflammation in rats. The present study was conducted to evaluate the anti inflammatory effect of TZDs (pioglitazone 3mg/Kg) on acute, sub acute and chronic model of inflammation by using egg-albumin and formalin–induced paw edema in 72 rats, relative to reference drugs Dexamethasone 5mg/Kg and Piroxicam 5mg/Kg. In each inflammation model, 24 rats were allocated into four subgroups, each containing six rats representing control, two standards, and test groups. All treatments were given (I.P) 30 minutes before induction of inflammation and the increase in paw edema was measured at certain time intervals by using vernier caliper. Pioglitazone produced nonsignificant reduction (P>0.05) of egg albumin-induced acute inflammation of the rat hind paw, while significantly produced time-related reduction of formalin-induced sub-acute and chronic inflammation of the rat hind paw. In conclusion, pioglitazone possesses anti-inflammatory activity in the animal models of sub-acute and chronic inflammations. Key Words: Pioglitazone, PPAR-γ, anti-inflammatory activity